Propuesta para la mejora de los tiempos entre recibo y preparación de mercancías en el centro de distribución de un operador logístico (2019)
The following degree project was carried out so that with the help of the tools of industrial engineering and its application in the distribution centers, the time of receipt and preparation of merchandise in a CEDIS can be reduced, this in order to increase the Productivity and improve the process. The CEDIS are collection centers where merchandise is handled before being distributed to more specific points for final consumption, throughout this work visits were made to the CEDIS in question analyzing and observing a specific process (Receipt of merchandise and preparation of orders for stores), this in order to characterize the process to make the necessary improvements in it. Through tools for the study of methods and times such as process, flow and transport diagrams, it was possible to show what the critical activities were in the development of the receipt of the merchandise, therefore this specific part of the process was the one that It was sought to improve, after proposing improvement options and comparing the improved process with the current one through the process and transport diagrams, it is possible to reduce the time of receipt of merchandise and with this increase the productivity of CEDIS and reduce operational costs in the development of its activities.